ALENT MANAGEMENT IN THE DIGITAL AGE: CHALLENGES AND OPPORTUNITIES - Onuorah, Onyeka Leo (Journal of the Management Sciences, 2023)
The digital age has significantly changed how organizations manage their talent. With the rise of digital technologies and remote work, organizations face new challenges in identifying, attracting, and retaining top talent. At the same time, digitalization presents new opportunities for talent management, such as increased access to global talent pools and data-driven decision-making. This paper explores the challenges and opportunities of talent management in the digital age and provides strategies for organizations to manage their talent in this new era effectively. The paper is qualitative research which adopted content analysis as a methodology. Data sources comprise the secondary sources of data collection. The paper analyzed empirical studies showing that a strong employer brand, data-driven decision-making, continuous learning and development opportunities, and a culture of inclusion and diversity are key digital talent management strategies. Organizations prioritizing these strategies are more likely to attract and retain top talent, foster innovation and agility, and ultimately achieve long-term success. With emerging trends and best practices and leveraging technology and data to inform decision-making, this study contends that organizations can be well-positioned to attract and retain top talent in an increasingly competitive talent market.